Flow-FISH using nucleic acid mimic probes for the detection of bacteria - Azevedo, Andreia S. (2021)
Flow-Fluorescence in situ hybridization (Flow-FISH) enables multiparametric high-throughput detection of target nucleic acid sequences at the single cell-level, allowing an accurate quantification of different cell populations by using a combination of flow cytometry and fluorescent in situ hybridization (FISH). In this chapter, a flow-FISH protocol is described with labeled nucleic acid mimics (NAMs) (e.g. LNA/2OMe and PNA) acting as the reporter molecules. This protocol allows for the specific detection of bacterial cells. Hence, this protocol can be carried out with minor adjustments, in order to simultaneously detect different species of bacteria in different types of clinical, food, or environmental samples.